(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Across sectional study was applied in Babylon teaching hospital for obstetric and children over six months period from April 2020 to September 2020 the study was done on 754 full term live birth neonate The birth wight and gestational age was taken for all newborn. The gestational age was calculated by last menstrual period and ultrasound examination and a new Ballard score. Full term is considered when the gestational age is ≥ 37 weeks Premature and infants with birth defects were excluded from the study Questionnaire was taken from mother whither attend ANC (antenatal care) or not and whither mother and father are smoker or not. The total number of low births weight was 69 from the total number full term which are 754 with a percentage of 9.2% and the number of large gestational age is 22 with a percentage of 2.9% . there is significant relationship between antenatal care and low birth weight with P-value <0.001 and also significant relationship between maternal smoking during pregnancy and low birth weight with P-value <0.001. but there is no relationship with paternal smoking.